Implementation of Smart Digital Finance in Promoting Digital Financial Inclusion and Risk Management - Louisa, Cindy Jasty (Journal of Economics, Social, and Humanities, 2026)
The development of digital finance has transformed financial systems in developing countries by enhancing efficiency, accessibility, and transparency, while simultaneously introducing new technological and institutional risks. This study analyzes the implementation of Smart Digital Finance in Indonesia and its role in promoting digital financial inclusion through the management of technological, trust, and security aspects. The study adopts a qualitative descriptive–analytical approach by systematically reviewing policy documents, institutional reports, and relevant academic literature. The findings indicate that the development of interoperable digital payment infrastructure, particularly through QR-based payment systems, has expanded public access to formal financial services, improved operational efficiency through the utilization of digital transaction data, and supported the integration of micro and small enterprises into the formal economic system. Nevertheless, cybersecurity risks, personal data protection issues, digital fraud, and public trust remain major challenges to the sustainability of the digital financial system. Therefore, this study emphasizes the importance of risk-sensitive regulation, strong consumer protection, secure digital identity systems, and effective institutional governance to ensure that Smart Digital Finance can promote inclusive economic growth and sustainable public financial governance in Indonesia.